2010
DOI: 10.1016/j.yhbeh.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress increases anxiety-like behavior in Balbc mice despite a compensatory increase in levels of postnatal maternal care

Abstract: A better understanding of the molecular and cellular mechanisms by which early life stress (ELS) modifies brain development and adult behavior is necessary for diagnosing and treating psychopathology associated with exposure to ELS. For historical reasons most of the work in rodents has been done in rats and attempts to establish robust and reproducible paradigms in the mouse have proven to be challenging. Here we show that under normal rearing conditions, increased levels of postnatal maternal care are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 63 publications
(76 reference statements)
8
94
1
1
Order By: Relevance
“…However, self-grooming can be seen as a de-arousing activity which is increased in anxious rats (Spruijt et al 1992;Kalueff and Tuohimaa 2005;Voigt et al 2005). Although the present design did not allow for analysing anxiety-related behaviour in dams, earlier studies demonstrated that offspring from dams previously exposed to a stress-inducing environment will show stronger responses to anxiogenic stimuli (Plotsky and Meaney 1993;Ladd et al 2000;Wei et al 2010;Maccari et al 2014;Barzegar et al 2015). Alternatively, grooming could also be associated with the significantly increased feeding as observed in the dams in the present study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, self-grooming can be seen as a de-arousing activity which is increased in anxious rats (Spruijt et al 1992;Kalueff and Tuohimaa 2005;Voigt et al 2005). Although the present design did not allow for analysing anxiety-related behaviour in dams, earlier studies demonstrated that offspring from dams previously exposed to a stress-inducing environment will show stronger responses to anxiogenic stimuli (Plotsky and Meaney 1993;Ladd et al 2000;Wei et al 2010;Maccari et al 2014;Barzegar et al 2015). Alternatively, grooming could also be associated with the significantly increased feeding as observed in the dams in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Instead, an U-shaped inverse relationship between environmental adversity and maternal care has been suggested. Above a certain level of adversity, environmental stress could affect the pups independently of maternal care (Macri and Wurbel 2006;Wei et al 2010). For example, it remains unclear from the present study, if, and to what extent, the enrichment procedure has a direct effect on the offspring.…”
Section: Discussionmentioning
confidence: 78%
“…Mating, BDS exposure, and observation of maternal behavior were done as described previously (Wei et al, 2010). In brief, animals were mated using a 2 : 1 female to male ratio with visibly pregnant dams placed individually in maternity cages with no nesting material.…”
Section: Brief Daily Maternal Separationmentioning
confidence: 99%
“…However, the establishment of early life stress paradigms that are associated with robust and reproducible behavioral outcomes in the mouse has proven to be a challenging task (Millstein and Holmes, 2007;Priebe et al, 2005), explaining the paucity of studies that have used unbiased genomic tools and transgenic animals to study this issue. We spent a significant effort to develop a robust early life stress paradigm in the mouse and recently showed that brief daily separation (BDS), in the highly stress-reactive mouse strain BALB/cByj, is associated with prolonged elevation of corticosterone during the postnatal period, abnormal hippocampal development, and robust behavioral changes in adulthood that occur despite a compensatory increase in maternal care (Wei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Важно, что даже после возвращения потомства к матери в экспери-менте на животных, уровень глюкокортикоидов в крови детенышей остается высоким, что результирует в нару-шении синтеза белков и пролиферации клеток в течение длительного периода [47], а также может обусловливать нарушение когнитивных функций.…”
unclassified